Endoscopic Sphenopalatine Artery Ligation in Recurrent Epistaxis with Hypertensio - Aini Zhann; Dolly Irfandy; Bestari Jaka Budiman; Deka Viotra (Faculty of Medicine, Universitas Andalas, 2023)
AbstractBackground: Epistaxis is the most common case in ORL-HNS emergencies. One of the risk factors of recurrent epistaxis is hypertension. Epistaxis in hypertension usually originates from the posterior vessels. This requires more invasive procedures such as sphenopalatine artery ligation. Case Report: A 58-year-old woman with complaints of recurrent epistaxis from the right nose. The results of the blood pressure examination showed the results of 190/120 mmHg. The patient underwent sphenopalatine artery ligation to prevent recurrence. Conclusion: One of the factors for recurrent epistaxis is hypertension. Initial management of epistaxis with recurrent hypertension can be done in a conservative way followed by surgery and keeping blood pressure stable. Endoscopic sphenopalatine artery ligation is the definitive treatment according to the epistaxis management algorithm. Endoscopic sphenopalatine artery ligation provides satisfactory results and minimal complications.Keywords: Recurrent epistaxis, hypertension, sphenopalatine artery ligation